Sistem Monitoring Daya Output Photovoltaic Berbasis IoT - Rouhillah; Rachmad Ikhsan; Furqan Farih (J-Innovation, 2022)
Solar panel monitoring systems are generally only through tools installed on the solar panel unit and carried out manually so that the parameters and data obtained are limited, and information cannot be obtained at any time. The purpose of this final project is to create a system that can monitor the performance of solar panels so that the utilization of solar panels becomes more effective, because through this monitoring system the early symptoms of damage can be detected early by humans. This tool is equipped with an INA219 sensor as a voltage and current detector, then the data will be processed by the NodeMCU ESP8266 microcontroller and then sent to the firebase. The data from the sensor readings will be displayed on the smartphone and can be viewed through the MIT APP application. This tool will also apply IoT technology as a monitoring method so that the data received will be displayed on the smartphone in real-time.